A democratic consensus? Isaiah Berlin, Hannah Arendt, and the anti-totalitarian family quarrel - Hiruta, K (Cambridge University Press, 2018)
Amid the ongoing political turmoil, symbolized by the recent violence in Charlottesville, Virginia, books and articles abound today to encourage us to re-read anti-totalitarian classics ‘for our times’. But what do we find in this body of work originally written in response to Nazism and Stalinism? Do we find a democratic consensus forged by a shared anti-totalitarian commitment? I doubt it. Considering the cases of Isaiah Berlin and Hannah Arendt, this article highlights discord beneath what may today appear like a post-war democratic consensus. I argue that the anti-totalitarian literature of the last century encompassed multiple political philosophies, which sometimes differed irreconcilably from each other.